Damage accumulation mechanism of composite laminates subjected to repeated low velocity impacts. (15th September 2020) - Liao, Binbin; Zhou, Jianwu; Li, Ying; Wang, Panding; Xi, Li; Gao, Ruxin; Bo, Ke; Fang, Daining
Highlights: The repeated low velocity impact responses for composite laminates were investigated. The variations of repeated impact-induced mechanical characteristics were studied. The damage behaviors with the increase of impact number were explored. A new damage index was proposed for characterizing the impact damage accumulation. Abstract: Composite structures used in ships and offshore equipment are subjected to repeated low velocity impacts at localized sites during service conditions. In this paper, the repeated low velocity impact responses and damage accumulation mechanism in the composite laminates were investigated by considering the effect of impactor diameter. The four impactors chosen had the diameters of 10 mm, 12 mm, 14 mm and 16 mm and the impact energy was set as 15 J for repeated impact tests. The mechanical responses such as impact force-time/central displacement curves during the tests were recorded until penetration occurred. The delamination projected area was measured using ultrasonic C-scan during the whole-process repeated impacts. Experimental results demonstrated that the delamination damage threshold at the first impact, large drop of impact force, and the constant plateau of impact force were the three typical characteristics of impact force-time/central displacement curves that corresponded to delamination initiation, fiber breakage, and penetration. Along with the impact number increasing, variations of the mechanical characteristics such as energy absorption, peak impact force, maximum central displacement and duration time were explored. A new damage index DI-B based on bending stiffness reduction rate R stiffness and normalized maximum displacement was proposed, which could characterize the damage accumulation of the current composite laminates and distinguish the occurrence of penetration by comparing with traditional characterization methods. Graphical abstract: Image, graphical abstract